Artificial sleep-like up/down-states induce synaptic plasticity in cortical neurons from mouse brain slices - Besing, Gai-Linn Kay; St. John, Emily Kate; Potesta, Cobie Victoria; Gallagher, Martin J.; Zhou, Chengwen (Frontiers in Cellular Neuroscience, 2022)
During nonrapid-eye movement sleep (NREM), neuron activity alternates between a depolarized (firing, up-state) and a hyperpolarized state (down-state) coinciding with delta EEG slow-wave oscillation (SWO, 0.5-4 Hz) in vivo. Recently, we have found that sleep-related up/down states can potentiate synaptic strength in neurons ex vivo. This work introduces an ex vivo method to induce homeostatic synaptic potentiation with sleep-related SWOs (up/down states) in cortical neurons. Using coronal brain slices, whole-cell voltage-clamp recordings were made from cortical pyramidal neurons to record spontaneous(s) excitatory synaptic currents (sEPSCs) and inhibitory synaptic currents (sIPSCs). Sleep-related up/down states (as SWOs, 0.5 Hz, 10 min, current-clamp mode) were induced by injecting sinusoidal currents into cortical neurons. Baseline pre-SWO recordings were recorded for 5 min and post-SWO recordings for at least 25-30 min. Compared to pre-SWO sEPSCs or sIPSCs, post-SWO sEPSCs or sIPSCs in cortical neurons exhibited significantly larger amplitudes and higher frequency for 30 min. This finding suggests that both sEPSCs and sIPSCs could be potentiated in neurons by the low-level activity of SWOs, and sEPSCs and sIPSCs maintained a balance in neurons during pre- and post-SWO periods. Overall, this study presents an ex vivo method to show the SWO’s ability to induce homeostatic synaptic potentiation in neurons, which may underlie sleep-related synaptic potentiation for sleep-related memory consolidation in vivo.